2005
DOI: 10.1186/1477-7827-3-38
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the true precocious puberty rats induced by neonatal administration of Danazol: Therapeutic effects of nourishing "Yin"- removing "Fire" Chinese herb mixture

Abstract: Background: Nourishing "Yin"-Removing "Fire" Chinese Herb Mixture, a traditional herb-based formulation, has been successfully used for the management of idiopathic true precocious puberty (IPP) for more than thirty years. Precocious puberty rat model by neonatal administration of Danazol was used to investigate the effects of the herb mixture on the advanced sexual development of the rats, and the expression of hypothalamic gonadotropin-releasing hormone (GnRH), which is the important regulator for the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…orientale Sam., Prunella vulgaris L., Carapax et Plastrum Testudinis, Fructus hordei germinate, and Gentiana scabra Bge) efficiently delayed pre-maturation in precocious puberty rats. 18 In the followed studies, Sun et al. reported that this herbal mixture suppressed the hypothalamic kisspeptin expression in danazol-induced precocious rats.…”
Section: Discussionmentioning
confidence: 99%
“…orientale Sam., Prunella vulgaris L., Carapax et Plastrum Testudinis, Fructus hordei germinate, and Gentiana scabra Bge) efficiently delayed pre-maturation in precocious puberty rats. 18 In the followed studies, Sun et al. reported that this herbal mixture suppressed the hypothalamic kisspeptin expression in danazol-induced precocious rats.…”
Section: Discussionmentioning
confidence: 99%
“…In humans and rats, the onset of puberty is caused by an increase in GnRH pulsed secretion. True PP is mediated by a premature increase in GnRH secretion and should be treated with a potent GnRHa ( Tian et al, 2005 ). The administration of exogenous kisspeptin can advance the puberty of immature rodent (rats) and primates (monkeys) ( Plant et al, 2006 ), on the contrary, administration of kisspeptin antagonist delayed puberty in rats and monkeys ( Skorupskaite et al, 2014 ; Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Danazol, a derivative of 17 α -acetylene testosterone, has an effect on the reproductive system of rats [ 25 ]. Studies have shown that the administration of danazol to newborn rats can rapidly promote the activation of the HPG axis [ 37 ], making them enter puberty earlier. Therefore, in this study, female SD rats at 5 days of danazol administration were used as the model to analyze the true precocious puberty.…”
Section: Discussionmentioning
confidence: 99%